Household sustainable consumption: an evaluation of environmental awareness materials - Caeiro, Sandra (2021)
European Union (EU) has been putting increasing emphasis on sustainable use and management of natural resources, especially since the adoption in 2001 of the EU Sustainable Development Strategy and the Sixth Environment Action Programme. Some objectives and priority areas for action are the achievement of a significant overall reduction in the volumes of waste generated through waste prevention initiatives, better resource exploitation efficiency and a shift towards more sustainable production and consumption patterns. There is wide global recognition that unsustainable patterns of consumption have serious social and environmental impacts. ‘Changing consumption patterns’, as identified by Chapter 4 of Agenda 21, remains a challenging, yet significant component of the drive to achieve sustainable development. Sustainable consumption does not mean about consuming less, it is about consuming differently, consuming efficiently, and having an improved quality of life. It also means sharing between the rich and the poor. The change of these consumption patterns could only be achieved through the use of correct and efficient environmental awareness/education campaigns. The purpose of the study is to conduct a state of the art of environmental awareness materials related with European household sustainable consumption. The search materials were compared and evaluated in terms of: aims; type of materials; target public; applicability and contents. The results of our research demonstrated that internet is a powerful tool and can contribute to the awareness of the general public about these issues. The problem of internet downloaded materials is the lack of their quality evaluation before them as available on the web. Weaknesses were found in terms of technical, scientific quality and their ability for learning-teaching. Some of them are very rudimentary, contributing little to the general public’s awareness. Also their interactivity could be better if taking into account the currently power of web base tools.